The effectiveness of judicial instructions on eyewitness evidence in sensitizing jurors to suggestive identification procedures captured on video - Skalon, Alena (Journal of experimental criminology, 2020)
One of the legal safeguards designed to educate jurors about eyewitness evidence is judicial instructions. However, their effectiveness in sensitizing jurors to eyewitness accuracy and suggestive identification procedures captured on video is unknown.